2007
DOI: 10.1111/j.1442-2042.2006.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based screening for prostate cancer by measuring total serum prostate‐specific antigen in Iran

Abstract: Objective: To report the results from an Iranian large population-based randomized study of screening using prostate-specific antigen (PSA) to detect prostate cancer. Materials and Methods: A total of 3758 Iranian men older than 40 years were mass checked by PSA-based screening. Men with an abnormal digital rectal examination (DRE) and serum total PSA level of greater than 4 ng/mL, underwent transrectal ultrasonography (TRUS)-guided extended prostate biopsy. Results: The PSA value (mean Ϯ standard deviation, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…Despite the racial discrepancies in serum PSA reference [23][24][25][26][27], we noticed that the proportion of PSA abnormalities in Asian countries is comparable to that in Western countries (Table 4), which was reported to be approximately 10% of men when a threshold PSA value of 4.0 ng/ml was used [1][2][3]28]. In this study, we found that 8.40% of screened subjects had serum PSA levels C4.0 ng/ml, a value similar to that in most of the other screening studies worldwide [6,15,17,20,24,[29][30][31][32]. In a metaanalysis reported by Mistry and Cable [28], the pooled PPV of PSA (with a cut-off value of 4.0 ng/ml) in asymptomatic men older than 50 years was calculated as 25.1% (range 17.0-57.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the racial discrepancies in serum PSA reference [23][24][25][26][27], we noticed that the proportion of PSA abnormalities in Asian countries is comparable to that in Western countries (Table 4), which was reported to be approximately 10% of men when a threshold PSA value of 4.0 ng/ml was used [1][2][3]28]. In this study, we found that 8.40% of screened subjects had serum PSA levels C4.0 ng/ml, a value similar to that in most of the other screening studies worldwide [6,15,17,20,24,[29][30][31][32]. In a metaanalysis reported by Mistry and Cable [28], the pooled PPV of PSA (with a cut-off value of 4.0 ng/ml) in asymptomatic men older than 50 years was calculated as 25.1% (range 17.0-57.0%).…”
Section: Discussionmentioning
confidence: 99%
“…1 In contrast to other Asian populations, 2,3 with a detection rate of 3.6-3.8%, the incidence of PCa in Iran is quite high. 4,5 It is well documented that genetic factors may account for as much as 42% of the PCa risk. 6 There are no consistent patterns of single chromosomal abnormalities in PCa; instead, the entire genome is apparently involved in prostatic carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…20 The lowest recorded PCa rate is 0.4 per 100 000 in Ardabil, northwest Iran. 13,21 Iranian men are ethnically and racially different from most of Asian men, 22 so the biochemical parameters of PCa should be different. In a study by Khezri et al, 23 in a large Iranian healthy male population, the serum PSA concentration correlated directly with the subject's age and prostatic volume.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 346 males with increased PSA values with or without positive DRE (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) A sextant biopsy was performed from the apex and base of the right and left parasagittal planes of the prostate with 10 core biopsies. If hypoechoic areas were noted on TRUS, a specimen was taken from each of these areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation